2012
DOI: 10.1002/qj.1905
|View full text |Cite
|
Sign up to set email alerts
|

Observed triggering of tropical convection by a cold surge: implications for MJO initiation

Abstract: The extratropical influence is an important mechanism in the initiation of the Madden-Julian Oscillation (MJO). Based on analyses of several datasets, this article demonstrates that the MJO case initiated in late January 2008 was strengthened by a preceding cold surge over West Asia when the MJO was at its initiation phase. The cold surge-related northerlies propagated southward along the east coast of Africa. The associated convergence on the edge of the surge enhanced ascending motion in the tropical western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…A number of theories regarding MJO initiation have been developed including boundary layer frictional convergence (Wang and Rui 1990), surface wind-evaporation feedbacks (Emanuel 1987;Neelin et al 1987), stochastic linearized convection and deep convective heating (e.g., Salby et al 1994), and influences from higher latitudes such as Rossby wave trains and cold-air outbreaks (Hsu et al 1990;Matthews and Kiladis 1999;Ray and Zhang 2010;Wang et al 2012). Topographic effects may be important for MJO initiation (e.g., Hsu and Lee 2005) and mean sea level pressure (MSLP) anomalies associated with dry Kelvin waves from previous MJO disturbances may help initiate a successive event (Matthews 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A number of theories regarding MJO initiation have been developed including boundary layer frictional convergence (Wang and Rui 1990), surface wind-evaporation feedbacks (Emanuel 1987;Neelin et al 1987), stochastic linearized convection and deep convective heating (e.g., Salby et al 1994), and influences from higher latitudes such as Rossby wave trains and cold-air outbreaks (Hsu et al 1990;Matthews and Kiladis 1999;Ray and Zhang 2010;Wang et al 2012). Topographic effects may be important for MJO initiation (e.g., Hsu and Lee 2005) and mean sea level pressure (MSLP) anomalies associated with dry Kelvin waves from previous MJO disturbances may help initiate a successive event (Matthews 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the origin of MJO initiation, there are two categories of hypotheses: those stressing tropical internal dynamics [e.g., a circumnavigating signal of the previous episode: Lau and Peng (1987); Wang and Li (1994); Kikuchi and Takayabu (2003); Matthews (2008); or local processes in the tropics: Hu and Randall (1994); Jiang and Li (2005); Straub (2013)] and those emphasizing extratropical forcing (e.g., Hsu et al 1990;Bladé and Hartmann 1993;Matthews and Kiladis 1999;Pan and Li 2007;Lin et al 2007;Ray and Zhang 2010;Wang et al 2012). Ray and Li (2013) evaluated the relative importance of circumnavigating signals and extratropical forcing by performing sensitivity experiments using a general circulation model and concluded that extratropical forcing was more important than were circumnavigating signals in association with mean moisture convergence.…”
Section: Introductionmentioning
confidence: 99%
“…These two PC time series are defined as the RMM index (Wheeler and Hendon 2004). Since the publication of the work (Wheeler and Hendon 2004), the RMM index has become the leading method for identifying the state of the MJO in observations (Jiang et al 2011;Riley et al 2011;Wang et al 2012;Straub 2013) and model analyses (Kim et al 2009;Gottschalck et al 2010).…”
Section: A Rmm Indexmentioning
confidence: 99%